Social Comparison and Distributive Justice: East Asia Differences - Kim, Tae-Yeol (Journal of business ethics, 2015)
Using a survey of 393 employees who were natives and residents of China, Japan, and South Korea, we examined the extent to which employees from different countries within East Asia experience distributive justice when they perceived that their work outcomes relative to a referent other (i.e., someone with similar “inputs” such as educational background and/or job responsibilities) were (1) equally poor, (2) equally favorable, (3) more poor, or (4) more favorable. As predicted, we found that when employees perceived themselves relative to a referent other to be recipients of more favorable outcomes (i.e., pay, job security), Chinese and Korean employees were less likely than Japanese employees to experience distributive injustice. We also found that these differences were partially mediated by employees’ level of materialism. Theoretical and practical implications of our findings are discussed.